Comparative analysis of routing techniques in chord overlay network - Omoruyi Osemwegie; Samuel John; Adewale Adeyinka; Etinosa Noma-Osaghae; Kennedy Okokpujie (Institute of Advanced Engineering and Science, 2021)
Overlay networks are not a new field or area of study. This domain of computing will someday drive P2P systems in various application areas such as block-chain, energy trading, video multicasting, and distributed file storage. This study highlights the two widely known methods of routing information employed in one of such overlay networks called chord. In this study, simulations of both routing modes (iterative and recursive) and their variations under no-churn (leaving and joining of nodes) and churn conditions was carried out. The routing parameter (successor list size) was varied for each of the routing techniques in a simulation study. The results obtained show that semi recursive routing gives a better routing performance under churn scenarios.